2022
DOI: 10.31234/osf.io/brn5s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time Pressure Reduces Misinformation Discrimination Ability But Does Not Alter Response Bias

Abstract: Evidence is accumulating that parts of our social lives are speeding up, a phenomenon known as social acceleration. The implications of social acceleration for people's ability to judge the veracity of online content, and ultimately for the spread of misinformation, are largely unclear. We examined the effects of accelerated online dynamics, operationalised as time pressure, on online misinformation evaluation. Participants judged the veracity of true and false news headlines in the presence or absence of time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…As in the context of climate change, this experiment revealed that deliberation did not increase political polarization; rather, people simply rated the fake news headlines as being less accurate when given the opportunity to deliberate (and this effect was again equivalent regardless of political consistency; Bago et al, 2020a). A recent experiment relying simply on time pressure produced similar results (Sultan et al, 2022) and increasing emotionality has also been shown to increase belief in fake news (Martel et al, 2020). These studies indicate that errors in judgments of the accuracy of news headlines often emerge because of faulty intuitions that are not sufficiently intervened upon by deliberation (see also Lutzke et al, 2019).…”
Section: Misinformation and Fake Newsmentioning
confidence: 64%
See 1 more Smart Citation
“…As in the context of climate change, this experiment revealed that deliberation did not increase political polarization; rather, people simply rated the fake news headlines as being less accurate when given the opportunity to deliberate (and this effect was again equivalent regardless of political consistency; Bago et al, 2020a). A recent experiment relying simply on time pressure produced similar results (Sultan et al, 2022) and increasing emotionality has also been shown to increase belief in fake news (Martel et al, 2020). These studies indicate that errors in judgments of the accuracy of news headlines often emerge because of faulty intuitions that are not sufficiently intervened upon by deliberation (see also Lutzke et al, 2019).…”
Section: Misinformation and Fake Newsmentioning
confidence: 64%
“…Furthermore, although there were only slight correlations with belief in true ("real") news, people who are more analytic were better at discerning between true and false news ("overall truth discernment"; Figure 7). The association between CRT and news discernment has been replicated in dozens of studies (Bowes & Tasimi, 2022;Brashier et al, 2021;Dias et al, 2020;Guay et al, 2022;Nurse et al, 2021;Pennycook, Bear, et al, 2020;Pennycook, Epstein, et al, 2021;Pennycook, McPhetres, et al, 2020;Pennycook & Rand, 2019b;Rosenzweig et al, 2021;Sultan et al, 2022;Tandoc et al, 2021) and has been extended…”
Section: Misinformation and Fake Newsmentioning
confidence: 80%
“…In these models, we treated sharing ("not share"/"share") as a binary response variable via a probit link function and assessed overall sharing tendency ( ; sharing across true and false news) as well as sharing quality ( ; sharing true over false news). Predicting overall sharing tendency and sharing quality aligns with recent recommendations in false news research (Guay et al, 2023) and mirrors the approach used in signal detection tasks, wherein behavior is characterized by both response bias and discrimination ability (Sultan et al, 2022). We report the mean and the 95% credible interval (CI) of the posterior distribution.…”
Section: News Sharing Behaviormentioning
confidence: 72%
“…Furthermore, although there were only slight correlations with belief in true ("real") news, people who are more analytic were better at discerning between true and false news ("overall truth discernment"; Figure 7). The association between CRT and news discernment has been replicated in dozens of studies (Bowes & Tasimi, 2022;Brashier et al, 2021;Dias et al, 2020;Guay et al, 2022;Nurse et al, 2021;Pennycook, Bear, et al, 2020;Pennycook, Epstein, et al, 2021;Pennycook, McPhetres, et al, 2020;Pennycook & Rand, 2019b;Rosenzweig et al, 2021;Sultan et al, 2022;Tandoc et al, 2021) and has been extended…”
Section: Misinformation and Fake Newsmentioning
confidence: 80%